Life Behavior of a System under Discrete Shock Model - Serkan Eryilmaz (Discrete Dynamics in Nature and Society)
We study the life behavior of a system which is subjected to shocks of random magnitudes over discrete time periods. We obtain the survival function and mean time to failure of the system assuming that the sizes of the shocks follow a discrete probability distribution under cumulative and mixed shock models.